Children's learning achievement and personality from the broken home family - Maghfirah Afifah; Neviyarni Suhaili; Irdamurni Irdamurni (Journal of Educational and Learning Studies, 2021)
This study aims to determine the learning achievement and personality of children from broken home families. This study uses a library research methodology. The writing of this article was carried out by reviewing as many as 13 national articles related to learning achievement and personality of broken home children in the family environment about the child's personality contained in the Google Scholar database. The results of the review were 13 articles. Family is the first educational institution responsible for providing education. The basic education provided by the family will determine the future of family life. It is also a place for children (family) to grow and develop as a whole. Without realizing it by parents that they have a very important role in educating children both in learning achievement and also in the child's personality, without realizing it, broken home families indirectly have a significant impact on their children. Very rarely do parents think about the consequences of that decision. Of the several impacts, the psychological impact is the most inherent. Even so, there are actually ways to overcome a broken home. This method will be effective for every family who wants a complete and harmonious family.